TOWARDS AN ASIAN HERMENEUTICS - L. Legrand (Asian Horizons, 2007)
This article draws our attention to two fundamental dimensions of biblical hermeneutics, namely, commitment to the poor and conversion to an Indian world vision. Rightly, Professor L. Legrand raises urgent and important questions in the context of dalits and tribals. The author invites our attention to different Asian zones having diverse religious concentration. Dr Legrand points out the important interpretation of the Word of God through textual and visual translations and transmissions. The author reminds the readers that a truly Indian interpretation will emerge as a component of a lively Asian hermeneutic that will bring to the Christian oikoumene a contribution proportionate to its global challenges and spiritual resources.